DEVELOPMENT OF WEBTOON APPLICATION-BASED MATH COMIC MEDIA (KOMIKA) IN LEARNING TO IMPROVE STUDENTS' NUMERACY LITERACY SKILLS: PENGEMBANGAN MEDIA KOMIK MATEMATIKA BERBASIS APLIKASI WEBTOON (KOMIKA) DALAM PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA - Sutini; Wahyuni Fajar Arum; Rifka Anisa (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
This research was conducted in response to the problems that seventh-grade students face in learning mathematics in the classroom, such as boredom and low achievement grades compared to the school's Minimum Completeness (KKM). The research aims to describe mathematics comic media's development process, validity, practicality, and effectiveness. The study was conducted at MTsN 2 Surabaya class VII G. The data collection techniques used were field notes, validation, response questionnaires, and test techniques. Furthermore, the research data obtained were analyzed using data analysis of field notes, validity, and practicality. Based on the results of the study, it was found that: (1) The process of developing math comics by using the Plomp development method. (2) The math comic media was declared "valid" with an average validity score of 3.534. (3) The math comic media was declared "practical" in the criteria of getting a "positive" response with a score of 81.79%. (4) The math comic media is declared effective because the percentage of learning completeness is above 70%, and there is an increase in students' numeracy literacy skills with an N-Gain value of 0.657. As for the effectiveness of the learning media itself, it can be seen from the results of the N-Gain test calculation which shows that the average value of the N-Gain Score is 0.657, including the moderate category with a minimum N-Gain value of 0.13 and a maximum of 1.00. So, using math comic media has a moderate effectiveness category with a percentage value of 44% in improving students' numeracy literacy skills.